Terapi Menulis Ekspresif untuk Meningkatkan Kesejahteraan Subjektif Remaja dengan Lupus - Fakhrisina Amalia Rovieq; Fuad Nashori; Yulianti Dwi Astuti (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Lupus is an autoimmune disease that affects the physical condition and the individual's psychological. Lupus makes teenagers tend to have low subjective well-being. One of the intervention methods to improve personal well-being is through expressive writing. This research aims to observe the effectiveness of expressive writing to improve teenagers' subjective well-being with lupus. This research used one group pretest post-test design involving four people as the subjects (N=4). The data were collected using the measurement tools of Scale of Positive and Negative Experience (SPANE), Satisfaction with Life Scale (SWLS), interview, observation, and the results of the writing of the subjects during the therapy session. The results of the experimental research were in the form of quantitative analysis with the data analysis technique of the K-related sample test, showing no significant change to the scores of the subjective well-being among the subjects after given the therapy of expressive writing. However, the qualitative results showed that definitive writing therapy could be a catharsis media for teenagers with lupus. Therefore, we can conclude that expressive writing is less effective in improving subjective well-being but can be used as a catharsis media for teenagers with lupus.